PELAKSANAAN SENTRA LITERASI DAN NUMERASI PADA ANAK USIA 4-5 TAHUN DI KB-TK LABSCHOOL JAKARTA - Zahra, Tifani Tiaraz; Rusdiyani, Isti; Maryani, Kristiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the observation that some children aged 4-5 years have not yet developed optimal literacy and numeracy skills. The study aims to describe the implementation of the learning center, the evaluation of learning, and the supporting and inhibiting factors associated with literacy and numeracy center activities for children aged 4-5 years at KB-TK Labschool Jakarta. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, interviews, documentation, and field notes. The results indicate that the literacy and numeracy center activities are conducted in a structured manner based on four stages: the play environment, pre-play, during-play, and post-play. Teachers act as facilitators who introduce concepts and guide the children while allowing them the freedom to choose their activities. Learning evaluation utilizes observation, documentation, anecdotal records, children's work samples, rating scales, and class list logs to assess child development. Supporting factors include the children's active engagement, varied learning media, and a conducive learning environment. Inhibiting factors include time constraints and the diversity of children's characteristics including children with special needs which are addressed through individualized approaches. The study concludes that the implementation of the literacy and numeracy center at KB-TK Labschool Jakarta has proceeded effectively, successfully stimulating children's literacy and numeracy skills through structured, child-centered play activities; it is hoped that these findings will serve as a reference for implementing effective practices to stimulate early childhood literacy and numeracy skills.